1998
DOI: 10.1515/zna-1998-10-1115
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Absolute Configuration of 1,5-Diaza-cis-decalin by Comparison of Measured and Calculated CD-Spectra

Abstract: The absolute configurations of both 1,5-diaza-c/s-decalin enantiomers were determined by com-parison of measured and calculated CD spectra. CD spectra for both enantiomers were recorded. Theoretical CD spectra for one of the isomers were calculated by means of the semiempirical CNDO/2S method. Eight local minima on the energy hypersurface of the title compound were used to describe the conformer equilibrium mixture. The geometries of these conformers were calculated employing one-determinant ab initio calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Ab initio calculations of electronic excitation energies were also done by the single excitation configuration interaction (CIS) procedure (Gaussian 98). CD spectra were simulated 24,[47][48][49] as sums of Gaussians centered at the wavelengths of the corresponding electronic transitions and multiplied by the calculated rotational strength. An empirical half bandwidth of 7 nm at 1/e of the maximum 24,49…”
Section: Methodsmentioning
confidence: 99%
“…Ab initio calculations of electronic excitation energies were also done by the single excitation configuration interaction (CIS) procedure (Gaussian 98). CD spectra were simulated 24,[47][48][49] as sums of Gaussians centered at the wavelengths of the corresponding electronic transitions and multiplied by the calculated rotational strength. An empirical half bandwidth of 7 nm at 1/e of the maximum 24,49…”
Section: Methodsmentioning
confidence: 99%
“…Hoffmann et al have independently shown that similar reaction conditions result in similar improvement (see ref a).…”
Section: Referencesmentioning
confidence: 87%
“…In the case of the 1,5-diaza- cis -decalins, the position of the equilibrium between the desired conformation capable of bidentate coordination, 11-in , and the other major conformation, 11-out , varies depending upon substituents (R), solvent, and additive. In an elegant study, Hoffmann and co-workers have shown that when the R groups are small, 11-in is favored and when the R groups are large, 11-out becomes favored. Regardless, the two conformations are energetically similar enough that the addition of acid or LiClO 4 shifts the equilibrium toward 11-in .…”
mentioning
confidence: 99%
“…In this study, all MTPA amides were processed as (Racid)-MTPA amides; that is, the dihedral angles of (Sacid)-MTPA amides cited in Table 1 were substituted by those of the mirror images (i.e., Racid-enantiomers) with plus/minus sign reversal [82]. Each of bis-and tetrakis-MTPA amides (i.e., CCDC 1280861 [55] [61], and CCDC 1294281 [56]), was processed individually. This procedure yielded 58 of (Racid)-MTPA amide moieties.…”
Section: Methodsmentioning
confidence: 99%
“…The MTPA amide moieties prepared from cyclic secondary amines exhibited the Z forms (i.e., CCDC 140352 [38] [54], and the two conformers of CCDC 1280861 [55]). …”
Section: Resonance Effects Of Amide Bond: C1′-n-c1-o1mentioning
confidence: 99%